The effect of the growth rate of birth population on Singapore housing market : an empirical study - Pua, Ki Fong (2018)
This study aims to explore the impact of birth population on future housing market in Singapore and provides a simple prediction on the housing market based on the given birth population and estimated economic conditions. To disclose the relationship between birth population and housing market, both public and private housing market, in term of housing demand and housing price, were examined. Given a gap of 28 years, OLS regression model with logarithm and first difference transformation was adopted to analyse the correlation between the growth rate of total births and the growth rate of housing demand and price. The analysis discovered several relationships, namely significant negative correlation on public housing demand, significant positive correlation on public housing price and private housing demand, whereas private housing price showed insufficient evidence to conclude the relationship with births. Overall, this paper suggested that birth population do affect the future housing market in Singapore, in particular demand and price of public housing, as well as demand of private housing. The outcome is critical for the Singaporean Government to take into account the growth rate of total births while deciding the policy on housing market to maintain the affordability of housing in Singapore.